Stereotactic ablative radiotherapy for the comprehensive treatment of 1–3 Oligometastatic tumors (SABR-COMET-3): study protocol for a randomized phase III trial - Olson, Robert; Mathews, Lindsay; Liu, Mitchell; Schellenberg, Devin; Mou, Benjamin; Berrang, Tanya; Harrow, Stephen; Correa, Rohann J. M.; Bhat, Vasudeva; Pai, Howard; Mohamed, Islam; Miller, Stacy; et al. (BMC cancer, 2020)
Background A recent randomized phase II trial evaluated stereotactic ablative radiotherapy (SABR) in a group of patients with a small burden of oligometastatic disease (mostly with 1–3 metastatic lesions), and found that SABR was associated with a significant improvement in progression-free survival and a trend to an overall survival benefit, supporting progression to phase III randomized trials. Methods Two hundred and ninety-seven patients will be randomized in a 1:2 ratio between the control arm (consisting of standard of care [SOC] palliative-intent treatments), and the SABR arm (consisting of SOC treatment + SABR to all sites of known disease). Randomization will be stratified by two factors: histology (prostate, breast, or renal vs. all others), and disease-free interval (defined as time from diagnosis of primary tumor until first detection of the metastases being treated on this trial; divided as ≤2 vs. > 2 years). The primary endpoint is overall survival, and secondary endpoints include progression-free survival, cost effectiveness, time to development of new metastatic lesions, quality of life (QoL), and toxicity. Translational endpoints include assessment of circulating tumor cells, cell-free DNA, and tumor tissue as prognostic and predictive markers, including assessment of immunological predictors of response and long-term survival. Discussion This study will provide an assessment of the impact of SABR on survival, QoL, and cost effectiveness to determine if long-term survival can be achieved for selected patients with 1–3 oligometastatic lesions. Trial registration Clinicaltrials.gov identifier: NCT03862911 . Date of registration: March 5, 2019,